PENGARUH PENURUNAN DOSIS DARI EKSTRAK ETANOL BATANG BROTOWALI (Tinospora crispa, L) TERHADAP EFEK ANTIPIRETIK PADA TIKUS PUTIH JANTAN GALUR WISTAR - Agustina Styawan, Anita; Budiman, Hendra (CERATA Jurnal Ilmu Farmasi, 2010)
Ethanol extract of brotowali stem (Tinospora crispa, L) contain 0,5% weight/volume had the same dosage as 0,1 g/kg body weight has the antipiretic effect. This research aimed to know about decrease dosage from ethanol extract of brotowali stem have the antipiretic effect and how the antipiretic potency compared with paracetamol to get effective dosage as antipiretic.Animal research used male albino rats strain Wistar by weight was 160-180 gram, age 2-3 months with sum 25 rats, which were devided into five groups of randomly, each group consist of 5 rats. The first group was used as an negative control given by aquadest 2 ml / 100 g body weight; 12,6 mg / 200 g body weight paracetamol was used as positive control in second group. Whereas the 3rd, 4th, and 5th group was given by ethanol extract brotowali stem containing 0,125%; 0,25%; and 0,5% weight/volume which had the same dosage as 0,025 g/kg body weight; 0,05 g/kg body weight; and 0,1 g/kg body weight. Infra red thermometer was used to measure rats temperature between the two side two legs of rats. Before the experiment, the first temperature of each rats was measured. DPT (Difteri Pertusis and Tetanus) vaccine 0,4 ml by subcutan injection were given to the fever rats. Two hours latter, the rats was treated by ethanol extract brotowali stem. The measurement of temperature rat body is conducted in every 15 minutes during 240 minutes. AUC (Area Under the Curve) was counted from temperature then statistically analized by test of homogeneity of variances and test of normaly distribution with Kolmogorov-Smirnov test then statistically analized ANAVA (analysis variances) and Tukey t test with confidence 95%.The result of this research is showing ethanol extract brotowali stem containing 0,5% weight/volume had same dosage as 0,1 g/kg body weight and 0,25% weight/volume had same dosage as 0,05 g/kg body weight have the antipiretic effect dan go down to ability more small than paracetamol. While ethanol extract brotowali stem contain 0,125% weight/volume had same dosage as 0,025 g/kg body weight haven’t the antipiretic effect. Key word : Antipiretic, brotowali stem, male albino rats strain Wistar.